The Politics of User-Driven Innovation: On innovative users, do-able needs, and frugal robots - Lipp, Benjamin (NOvation — Critical Studies of Innovation, 2022)
Users play an increasingly important role in European innovation policy. They are commonly seen as drivers of and active co-creators within innovation processes. However, user-driven innovation remains infused with a number of assumptions about users, technology, and “successful” innovation, which (partly) undermine a more democratic, open approach to innovation. In this contribution, I investigate the interplay between broader policy assumptions in the European discourse on user-driven innovation and its practical performance within an innovation project centring on healthcare robotics. Here, I argue that the politics of user-driven innovation harbours particular assumptions that, in effect, restrict the agency of users while also engendering conflict and contradictory outcomes. Hence, user-driven innovation is not simply about users driving innovation but rather about interfacing users and their concerns with (robotics) developers and their technology. For this, I propose an analytics of interfacing, which draws together literatures on the performative dynamics of participatory processes and more recent work on the political economy of participation. Here, I contend that it is not enough to investigate the construction and performance of publics; rather, it is additionally necessary to follow the manifold practices by which those publics are rendered available for certain technological solutions – and vice versa. Such an analytical approach opens up a fruitful avenue to critically enquire into the politics of participation – sitting in between innovation policy and practice.